A Remark on the Completeness of Systems of Exponentials with Weight in $L^2(ℝ)$ - Vynnyts’kyi, B. V.; Shapovalovskii, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish new conditions for the completeness of systems of exponentials with weight in L 2(ℝ), which complement and generalize the results obtained earlier by the authors.